(untitled) (Indian Journal of Arid Horticulture, 2025)
Water is the most critical input for horticultural productivity, and efficient use of water is critical for the development of sustainable horticulture. The efficiency of irrigation water use continues to be low with adverse environmental repercussion. Increasing water- use efficiency through improved irrigation systems as an alternative or a complement to physically enhanced water supplies is an important issue in water resource management. Micro-irrigation has emerged as an appropriate water saving techniques for all wide spaced high value crops in water scarce, undulated and sandy areas of hot arid ecosystem. This paper deals with the present status of micro-irrigation research, economics of different micro-irrigation systems and the need for affordable and low cost micro-irrigation systems. Future research on micro-irrigation is needed (i) to improve the performance of drip system, and (ii) to include fertigation study. The various studies revealed that the productivity of horticultural crops can be enhanced to the tune of about 60-70 percent by adopting micro-irrigation.